Perancangan Alat Pencegah Kebakaran Rumah Akibat Kelalaian Manusia Mematikan Kompor Gas Berbasis Mikrokontroler Arduino yang Terintegrasi dengan Smartphone - Surawan Setiyadi; Dendra Alfi Nugroho (Journal of Electrical And Electronics Engineering, 2021)
Many know that the activities of most people who are at home certainly cannot be kept away from the name of cooking with gas stoves. But it was a concern because of the many cases that occurred related to gas stoves. Often from most people when cooking they forget to turn off the stove because of other activities or even leave. This can lead to potential house fires. To overcome this problem, we need a tool that can detect the condition of the gas stove, in order to prevent undesirable things from happening earlier. To avoid undesirable events due to human negligence turning off the gas stove. So the design of making tools that can determine whether there is activity of moving objects in front of the gas stove. So that if the gas stove is still burning, the gas stove will automatically turn off or be turned off remotely by the homeowner by giving notification to the homeowner's handphone.